Amine degradation in CO2 capture. 4. Development of complementary analytical strategies for a comprehensive identification of degradation compounds of MEA. (November 2015) - Cuzuel, Vincent; Gouedard, Camille; Cuccia, Lorena; Brunet, Julien; Rey, Aurélien; Dugay, José; Vial, Jérôme; Perbost-Prigent, Frédérique; Ponthus, Jérémie; Pichon, Valérie; Carrette, Pierre-Louis
Highlights: Study of MEA degradation products from pilot plants. Six complementary analytical methods were developed. 59 degradation products were observed including 26 which were not cited in previous studies. Application of this strategy for routine analysis of real samples. Abstract: CO2 capture and storage are quite a promising approach to limit greenhouse gas emission. However CO2 capture process relies on the use of amine solutions which are likely to degrade and produce potentially harmful compounds. To ensure an environmental acceptance and to understand this degradation, analytical methods are needed to identify and quantify as many as possible of these products. In our study, monoethanolamine was used as a model compound for CO2 capture. Therefore an analytical strategy was developed to provide the most exhaustive list of degradation products. It was based on the complementarity between liquid and gas chromatography coupled with various mass spectrometry ionization and detection modes... This analytical strategy enabled the identification of 59 degradation products in pilot plant samples, but 26 of which were never reported. It provides also key information to develop quantification methods for pilot or industrial plant monitoring.